Irradiation of the subventricular zone and subgranular zone in high- and low-grade glioma patients: an atlas-based analysis on overall survival. Issue 1 (13th January 2022) - Bruil, Danique E; David, Szabolcs; Nagtegaal, Steven H J; de Sonnaville, Sophia F A M; Verhoeff, Joost J C
Abstract: Background: Neural stem cells in the subventricular zone (SVZ) and subgranular zone (SGZ) are hypothesized to support growth of glioma. Therefore, irradiation of the SVZ and SGZ might reduce tumor growth and might improve overall survival (OS). However, it may also inhibit the repair capacity of brain tissue. The aim of this retrospective cohort study is to assess the impact of SVZ and SGZ radiotherapy doses on OS of patients with high-grade (HGG) or low-grade (LGG) glioma. Methods: We included 273 glioma patients who received radiotherapy. We created an SVZ atlas, shared openly with this work, while SGZ labels were taken from the CoBrA atlas. Next, SVZ and SGZ regions were automatically delineated on T1 MR images. Dose and OS correlations were investigated with Cox regression and Kaplan-Meier analysis. Results: Cox regression analyses showed significant hazard ratios for SVZ dose (univariate: 1.029/Gy, P < .001 ; multivariate: 1.103/Gy, P = .002 ) and SGZ dose (univariate: 1.023/Gy, P < .001 ; multivariate: 1.055/Gy, P < .001 ) in HGG patients. Kaplan-Meier analysis showed significant correlations between OS and high-/low-dose groups for HGG patients (SVZ: respectively 10.7 months (>30.33 Gy) vs 14.0 months (<30.33 Gy) median OS, P = .011 ; SGZ: respectively 10.7 months (>29.11 Gy) vs 15.5 months (<29.11 Gy) median OS, P < .001 ). No correlations between dose and OS were found for LGG patients. Conclusion: Irradiation doses on neurogenic areas correlate negatively with OS in patients with HGG. Whether sparing of the SVZ and SGZ during radiotherapy improves OS, should be subject of prospective studies.